2005
DOI: 10.1159/000089435
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Patients and Cardiovascular Problems: Can Technology Help Solve the Complex Equation?

Abstract: Patients with end-stage kidney disease undergoing chronic hemodialysis (HD) present higher mortality rates compared with the general population. Once patients are on HD, the risk of cardiovascular death is approximately 30 times higher than in the general population and remains 10–20 times higher after stratification for age, gender, and the presence of diabetes. About half the deaths of patients on dialysis are attributed to cardiovascular causes including coronary heart disease, cerebrovascular disease, peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 93 publications
0
9
0
1
Order By: Relevance
“…23 Nonetheless, the dialysis population continues to carry an excess mortality from fatal cardiovascular events. 24 We found that plasma ADMA levels were increased by both dialysis treatment and that plasma ADMA levels were negatively correlated with NOx levels. However, the effects of dialysis models on both plasma ADMA and NO are controversial.…”
Section: Discussionmentioning
confidence: 64%
“…23 Nonetheless, the dialysis population continues to carry an excess mortality from fatal cardiovascular events. 24 We found that plasma ADMA levels were increased by both dialysis treatment and that plasma ADMA levels were negatively correlated with NOx levels. However, the effects of dialysis models on both plasma ADMA and NO are controversial.…”
Section: Discussionmentioning
confidence: 64%
“…A single HD session in itself causes acute cardiovascular stress with multiple effects on the patient ranging from an increase in both cardiac frequency and risk of arrhythmic events to variations in the vascular tone with sudden changes in systemic arterial pressure, and the release of cytokines by the circulating cells that come into contact with the extracorporeal circuit [4,13] . With the above considerations taken as a starting point, and to standardize haemodynamic stress, our patients were treated with haemodiafiltration, a wellknown and highly effective type of dialysis, displaying both diffusion and convection processes, which guarantees a greater biocompatibility and cardiovascular tolerance [14,15] . Thanks to its strategic localization, the endothelium is the first organ to sense mechanical stimuli, such as pressure and shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…Uremic-related factors include albuminuria, hyperhomocysteinemia, elevated lipoprotein(a), interleukin-6, anemia, abnormal calcium/phosphate metabolism, extracellular fluid volume overload, electrolyte imbalance, oxidative stress, inflammation (C-reactive protein), malnutrition, thrombogenic factors, and altered nitric oxide/endothelin balance [13,14,15,16]. With regard to the dialysis technique, some of the proposed parameters that might modulate the CV risk are: use of high-flux dialyzers, endotoxin filters, hemodiafiltration, non-catheter access type, adequate dialysis doses, and longer or more frequent sessions [17]. …”
Section: Introductionmentioning
confidence: 99%